Protective Effect of Nasal Colonisation with ∆cps/piaA and ∆cps/proABC Streptococcus pneumoniae Strains against Recolonisation and Invasive Infection - Ramos-Sevillano, Elisa (Vaccines (Basel), 2021)
Rationale: Nasopharyngeal administration of live virulence-attenuated Streptococcus pneumoniae strains is a potential novel preventative strategy. One target for creating reduced virulence S. pneumoniae strains is the capsule, but loss of the capsule reduces the duration of S. pneumoniae colonisation in mice which could impair protective efficacy against subsequent infection. Objectives: To assess protective efficacy of nasopharyngeal administration of unencapsulated S. pneumoniae strains in murine infection models. Methods: Strains containing cps locus deletions combined with the S. pneumoniae virulence factors psaA (reduces colonisation) or proABC (no effect on colonisation) were constructed and their virulence phenotypes and ability to prevent recolonisation or invasive infection assessed using mouse infection models. Serological responses to colonisation were compared between strains using ELISAs, immunoblots and 254 S. pneumoniae protein antigen array. Measurements and Main Results: The ∆cps/piaA and ∆cps/proABC strains were strongly attenuated in virulence in both invasive infection models and had a reduced ability to colonise the nasopharynx. ELISAs, immunoblots and protein arrays showed colonisation with either strain stimulated weaker serological responses than the wild type strain. Mice previously colonised with these strains were protected against septicaemic pneumonia but, unlike mice colonised with the wild type strain, not against S. pneumoniae recolonisation. Conclusions: Colonisation with the ∆cps/piaA and ∆cps/proABC strains prevented subsequent septicaemia, but in contrast, to published data for encapsulated double mutant strains they did not prevent recolonisation with S. pneumoniae. These data suggest targeting the cps locus is a less effective option for creating live attenuated strains that prevent S. pneumoniae infections.